2012
DOI: 10.1007/s00276-012-0946-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical basis of the risk of injury to the right laryngeal recurrent nerve during thoracic surgery

Abstract: Intraoperative incidence of right laryngeal recurrent nerve direct injury could be decreased by understanding the detailed course of its intrathoracic part. Moreover, traction on the intrathoracic part of the right vagus nerve may result in indirect lesions of the right laryngeal recurrent nerve: stretch induced lesions and nerve vasculature's lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Intraoperative removal of the paratracheal and upper thoracic paraesophageal lymph node groups in the upper mediastinum may be complicated by damaging the recurrent laryngeal nerves. Our data regarding the vertebral level of the loop of the right recurrent laryngeal nerve across the subclavian artery are consistent with other observations [ 2 ] that it is most common at the T1 vertebral level; other investigators found it more common at the T1–T2 (43%) or T2 (43%) level [ 15 ]. As our anatomic and clinical observations show, the upper mediastinum's recurrent laryngeal nerve generally has a fairly typical course.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Intraoperative removal of the paratracheal and upper thoracic paraesophageal lymph node groups in the upper mediastinum may be complicated by damaging the recurrent laryngeal nerves. Our data regarding the vertebral level of the loop of the right recurrent laryngeal nerve across the subclavian artery are consistent with other observations [ 2 ] that it is most common at the T1 vertebral level; other investigators found it more common at the T1–T2 (43%) or T2 (43%) level [ 15 ]. As our anatomic and clinical observations show, the upper mediastinum's recurrent laryngeal nerve generally has a fairly typical course.…”
Section: Discussionsupporting
confidence: 92%
“…Topographic deviation of the posterior mediastinum in the patient’s prone position with an iatrogenically induced collapse of the right lung increases the possibility of accidental damage to critical anatomical structures that run close to the esophagus. Therefore, to safely perform thoracoscopic procedures on the esophagus, it is necessary to highlight the prominent anatomic landmarks that allow the surgeon to reliably and safely navigate through the mediastinal adipose tissue spaces near the great vessels and nerves [ 2 , 3 , 5 ]. However, a systematic description of the essential anatomic landmarks for thoracoscopic navigation during esophageal extirpation is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 53 studies ( n  = 53,577 total nerves; 33,571 Right RLNs and 20,006 Left RLNs) were included: 35 intraoperative, 17 cadaveric and 1 imaging (CT) (Reed, 1943; Wade, 1955; Hunt, Poole & Reeve, 1968; Stewart, Mountain & Colcock, 1972; Skandalakis et al, 1976; Papadatos, 1978; Proye et al, 1982; Flament, Delattre & Palot, 1983; Henry et al, 1988; Menck, Grüber & Lierse, 1990; Lekacos et al, 1992; Freschi et al, 1994; Moreau et al, 1998; Sasou, Nakamura & Kurihara, 1998; Sturniolo et al, 1999; Campos & Henriques, 2000; Raffaelli, Iacobone & Henry, 2000; Watanabe et al, 2001; Watanabe et al, 2016; Monfared, Gorti & Kim, 2002; Page, Foulon & Strunski, 2003; Hermans et al, 2003; Ardito et al, 2004; Toniato et al, 2004; Spartà et al, 2004; Sciumè et al, 2005; Shindo, Wu & Park, 2005; Beneragama & Serpell, 2006; Maranillo et al, 2008; Makay et al, 2008; Serpell, Yeung & Grodski, 2009; Lee et al, 2009; Sunanda, Tilakeratne & De Silva, 2010; Shao et al, 2010; Wang et al, 2011; Kaisha, Wobenjo & Saidi, 2011; Kandil et al, 2011; Pradeep, Jayashree & Harshita, 2012; Chiang et al, 2012; Tang et al, 2012; Benouaich et al, 2012; Asgharpour et al, 2012; Silva, Siqueira & Arruda, 2013; Donatini, Carnaille & Dionigi, 2013; Satoh et al, 2013; Cai et al, 2013; Hong, Park & Yang, 2014; Yang et al, 2014; Han, Bai & Lu, 2015; Dolezel et al, 2015; Iacobone et al, 2015; Buła et al, 2015; Ngo Nyeki et al, 2015; Barczyński et al, 2015). The dates of the included studies spanned the period from 1943 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of the NRLN has been reported numerous times with rates ranging from 0% to 4.76% (Menck, Grüber & Lierse, 1990; Freschi et al, 1994; Moreau et al, 1998; Sasou, Nakamura & Kurihara, 1998; Sturniolo et al, 1999; Monfared, Gorti & Kim, 2002; Page, Foulon & Strunski, 2003; Makay et al, 2008; Lee et al, 2009; Kandil et al, 2011; Benouaich et al, 2012; Ngo Nyeki et al, 2015). It is essential to obtain accurate anatomical data on the NRLN if patients with this anomaly are to be assessed properly for surgical candidacy and operative planning.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of the NRLN has been reported numerous times with rates ranging from 0% to 4.76% (Menck, Grüber & Lierse, 1990;Freschi et al, 1994;Moreau et al, 1998;Sasou, Nakamura & Kurihara, 1998;Sturniolo et al, 1999;Monfared, Gorti & Kim, 2002;Page, Foulon & Strunski, 2003;Makay et al, 2008;Lee et al, 2009;Kandil et al, 2011;Benouaich et al, 2012;Ngo Nyeki et al, 2015). It is essential to obtain accurate anatomical data on the NRLN if patients with this anomaly are to be assessed properly for surgical candidacy and operative planning.…”
Section: Introductionmentioning
confidence: 99%